A Bayesian model comparison approach to test the specificity of visual integration impairment in schizophrenia or psychosis. (July 2018) - Grove, Tyler B.; Yao, Beier; Mueller, Savanna A.; McLaughlin, Merranda; Ellingrod, Vicki L.; McInnis, Melvin G.; Taylor, Stephan F.; Deldin, Patricia J.; Tso, Ivy F.
Highlights: Within the schizophrenia-bipolar-healthy spectrum, visual integration impairment is characteristic of psychosis and not specific to schizophrenia or traditional diagnostic categories. Visual integration impairment may share similar disease pathways with abnormal neurocogniton in psychosis. Bayesian model comparisons provide a statistical approach to extract common psychopathological dimensions across diagnostic groups. Abstract: Impaired visual integration is well documented in schizophrenia and related to functional outcomes. However, it is unclear if this deficit is specific to schizophrenia, or characteristic of psychosis more broadly. To address this question, this study used a Bayesian model comparison approach to examine the evidence of three grouping models of visual integration performance in 116 individuals with schizophrenia (SZ), schizoaffective disorder (SA), bipolar disorder (BD) with or without a history of prominent psychosis (BDP+ and BDP-, respectively), or no psychiatric diagnosis (healthy controls; HC). We compared: (1) Psychosis Model (psychosis, non-psychosis), where the psychosis group included SZ, SA, and BDP+, and the non-psychosis group included BDP- and HC; (2) Schizophrenia Model (SZ, non-SZ); and (3) DSM Model (SZ, SA, BD, HC). The relationship between visual integration and general cognition was also explored. The Psychosis Model showed the strongest evidence, and visual integration was associated with general cognition in participants with psychosis. The results were consistent with the Research Domain Criteria (RDoC) framework, indicating that visual integration impairment is characteristic of psychosis and not specific to SZ or DSM categories, and may share similar disease pathways with observed neurocognitive deficits in psychotic disorders.